HR Performance Improvement Based on Talent Management, Servant Leadership and Organizational Commitment - Satriadi Satriadi; Ersa Cahyu Marcelyna; Rahmanisa Rahmanisa; Marhalinda Marhalinda; Sumardin Sumardin (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study is to analyze the improvement of work based on talent management, servant leadership through organizational commitment. The type of research used is qualitative research. Research shows that talent management has a positive impact on leadership engagement that serves has a positive impact on organizational commitment, HR performance improvement based on talent management and servant leadership has a positive impact on organizational commitment, effective talent management, servant leadership has a positive impact on HR results. Talent management and servant leadership have a positive effect on staff performance and organizational commitment positive impact on HR performance Organizational commitment cannot be transferred the influence of organizational culture on the performance of personal activities. The effect of this research can be said to have theoretical and practical implications, there are efforts to improve the quality of HR performance maintaining and developing various organizational fronts with company needs.